Translator Mobile App for Teaching Children of Beginner-Level -French. - Alina NEPEMBE; Leena KLOPPERS; Jude OSAKWE (Journal of Information System and Informatics, 2020)
Living in the digital era and in a society that recognises the importance of technology, Information and Communications Technology (ICT) plays a major role in almost every point of life and particularly in education. Teachers play a major role in the teaching and learning of foreign languages. Mobile applications open new opportunities for learning how to read and speak different languages. One such mobile application that is used in education to facilitate learning of new language is the mobile translator. Although, there are numerous language translator applications that are freely available online, most of them have different shortcomings. This study focused on filling the gap of different shortcomings presented by different translator applications and specifically cater the mobile application for the FNCC curriculum. The main objective of this study was to design and develop a mobile translator application to facilitate the effective teaching of beginner level French for children at FNCC. Interviews were carried out as a data collection method to identify the requirements for the mobile translator application. The French teachers at the FNCC (Franco Namibia Cultural Centre) served as a sample group. Purposive sampling method was used to identify the participants and two teachers were selected. The application was developed following the incremental process model, an android mobile application was designed and developed, the application was evaluated using the PACMAD usability model, the incremental testing were adopted. The findings of the research show that there are different teaching strategies used in teaching and learning of French. Features were incorporated on the mobile application that are believed to enhance teaching and learning of French at beginner level. The PACMAD usability model determined what other French applications (which were purposively selected) lack and a comparison was carried out between the selected applications. The results of the comparison determined what should be included in the French mobile application for beginner level for children at the FNCC.